2018
DOI: 10.4103/jmu.jmu_11_18
|View full text |Cite
|
Sign up to set email alerts
|

A single static breast model education of ultrasound skill in final year medical students of Burapha University

Abstract: Background:Ultrasound (US) is widely used among physicians. There has been no standardized curriculum in US for undergraduate medical students. This study aimed to assess the US image acquisition skill of final year medical students after adding 2 weeks dedicated radiology rotation.Methods:At our institution, there are two hospital affiliations. Two-week radiology rotation was added for the final-year students of one affiliation. These students had a chance to do the US in real-life clinical settings proctored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Limchareon S et al showed the beneficial effect of a two-week rotation training in radiology on 48 student's US skills, regardless of their baseline performances. They also used the OSCE as a standardized assessment tool [18]. Ault et al performed a breast workshop focusing on physical examination, mammography and US interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Limchareon S et al showed the beneficial effect of a two-week rotation training in radiology on 48 student's US skills, regardless of their baseline performances. They also used the OSCE as a standardized assessment tool [18]. Ault et al performed a breast workshop focusing on physical examination, mammography and US interpretation.…”
Section: Discussionmentioning
confidence: 99%